Multi-scenario Cost Benefit Analysis for Water & Energy Utilities Infrastructure Based on Flood Mitigation Software (FaMOUS) - Sidek L.M.; Basri H.; Rostam N.E.B.; Ahmad R.D.R.; Marufuzzaman M.; Rohaizi M.S.; Suhaimi N.A.M. (Springer Science and Business Media Deutschland GmbH, 2024)
This paper focuses on flood risk analysis, flood impact, updating information related to Assets Inventory Database and measuring the damage to multi-scenarios costbenefit analysis for the affected water and energy infrastructure. This software can play a major role in maintaining the database, creating various analysis before and after flood policies, and suggesting the flood risk and damage cost. Furthermore, flood significantly affects the water and energy infrastructure of numerous utility providers. Previously, many strategies have already been devised to predict the risk of floods and their repercussions. These have provided new insights or conducted costbenefit analyses for flooding prevention techniques. Nevertheless, decision-making for diverse flood control methods is vital due to the high expense. As a result, multiple-scenario costbenefit analysis approaches would support decision-making on a preferred flood mitigation system to reduce the flood hazard to their assets. The main objective of this study is to create a system called FaMouS (Flood Mitigation System) as the high expense makes decision-making for diverse flood control methods important, perform a costbenefit analysis, prioritize mitigation measures, and provide tools to estimate and assist energy and water infrastructure owners in protecting their assets operationally. This software incorporates a variety of mitigation methods with CostBenefit Analysis to assist stakeholders in prioritizing the best mitigation measures. Hence, this software has given a better flood damage analysis and create a flood mitigation system compared to past plans and methods which had not given such results of flood costbenefit analysis in Multi-Scenario. The survey results prove that the Famous software can be recommended and applied to all flood-risk areas in Malaysia. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.